2010
DOI: 10.1007/s12272-010-1117-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of visnagin in lipopolysaccharide-stimulated BV-2 microglial cells

Abstract: Visnagin, which is found in Ammi visnaga, has biological activity as a vasodilator and reduces blood pressure by inhibiting calcium influx into the cell. The present study demonstrates the anti-inflammatory effect of visnagin on lipopolysaccharide (LPS)-stimulated BV-2 microglial cells. When cells were treated with visnagin prior to LPS stimulation, production of nitric oxide and expression of iNOS were attenuated in a dose-dependent manner. Visnagin also caused a significant decrease of mRNA expression and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 34 publications
4
22
0
1
Order By: Relevance
“…Khellin is a vasodilator and bronchodilator [12]. It has been implicated, along with its chemical relative visnagin, in the inhibition of nuclear factor κB [13]. It is an anti-inflammatory agent, and its mechanism of action is blocking the calcium channel in cells [11].…”
Section: Resultsmentioning
confidence: 99%
“…Khellin is a vasodilator and bronchodilator [12]. It has been implicated, along with its chemical relative visnagin, in the inhibition of nuclear factor κB [13]. It is an anti-inflammatory agent, and its mechanism of action is blocking the calcium channel in cells [11].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that VIS can protect kidney epithelial cells from damage by oxalate and protect neurons from kainic acid-induced apoptosis (22, 23). Furthermore, VIS has been shown to inhibit LPS-stimulated inflammation in a microglial cell line (24). Very little is known about the biological function and target of DPU.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds exhibit vasodilatory activities due to their calcium channel blocking properties [15,16] and act in an anti-inflammatory manner by inhibiting AP-1 and NF-κB signaling [17]. Khellin has been extensively used by the pharmaceutical industry as basic raw material for the development of drugs such as the anti-asthmatic agent sodium cromoglycate or the widely used anti-arrhythmic drug amiodarone [18].…”
Section: Introductionmentioning
confidence: 99%